STRATEGI KOMUNIKASI DINAS PERHUBUNGAN DALAM MENSOSIALISASIKAN APLIKASI SIP TB (TRANSBATAM) DI KOTA BATAM - Khotimah, Chusnul Khotimah (LPPM Universitas Putera Batam, 2023)
Transportation needs are increasing in Batam City. To make it easier for the community, the Batam City Transportation Service has supported the availability of public transportation facilities. Public transportation available in Batam City is quite diverse including Trans Batam (TB), public transportation (City Transportation), city buses and others. However, until now Batam City is still very minimal in providing information services regarding transportation, such as routes, departure schedules, area coverage and others. Based on the research conducted, it has been found various problems experienced by public transportation users in Batam. The main problem found in this case is the lack of detailed information about public transportation in Batam City. Therefore the Department of Transportation innovates to design an application called SIP TB with the hope that the output of the application is in accordance with the needs and desires of users. The method used in this study is a qualitative method using data collection techniques, observations and interviews. In this study, proving that the SIP TB application can provide convenience to users of public transportation (especially Trans Batam) where people can access information about Trans Batam transportation in real time. Keywords: SIP TB application; Department of Transportation; Media Channels; Communication Strategy; Transportation.